Frequency stability analysis of power system with photovoltaic frequency regulation considering communication delay - Yang, Zhichun; Hu, Wei; Yang, Fan; Liu, Ruifan (Frontiers in Energy Research, 2023)
Photovoltaic (PV) grid-connected will reduce the inertia of the system, which has an effect on power system frequency reliability. In order to clarify the frequency stability situation of power system when photovoltaic participates in frequency regulation, this paper first establishes the load frequency control (LFC) model of the power system with photovoltaic based on the analysis of the traditional LFC model of the power system. Secondly, based on the Pade approximation method, the communication delay in the control loop is linearized. The frequency stability of power system with photovoltaic participation in frequency regulation is characterized by system frequency steady-state error, feedback system sensitivity, and closed-loop system stability margin. According to the index calculation and theoretical derivation, the influence of system frequency regulation related parameters on frequency characteristics is analyzed. Finally, on the matlab/simulink simulation environment, the frequency stability methodological approach presented in this research is validated. The results of the simulations demonstrate the effectiveness of this analytical approach in assessing the frequency stability of a power system with photovoltaic frequency regulation while taking communication latency into account. It can provide guidance for the power grid’s secure operation and control when photovoltaics participate in frequency regulation.